Environmental aspects of the process of shaping the new common agricultural policy - Karol Kociszewski (Economic and Environmental Studies (E&ES), 2012)
The increasing importance of ecological and environmental protection policies, as well as the corresponding social preferences and action taken by non-governmental organizations, have contributed to the enhanced role of pro-ecological solutions implemented as a part of the European Union's Common Agricultural Policy (CAP). However, on the basis of analysis of official EU documents and bills relating to the 2014-2020 CAP reform, it can be argued that the importance of the aforementioned factors has diminished compared to the reform bill originally proposed by the European Commission. This may be the result of the opposing stand taken by the European Parliament as a consequence of the special interests of those states with a relatively large share of agriculture in their economies and the influence of the food processing industry lobby. As a result, the scope and effectiveness of some instruments of substantial importance (specifically those implemented as a part of the second pillar of the CAP) will rely on internal policies exercised by individual Member States.
Keywords: 330; Common Agricultural Policy reform; environmental protection in agriculture; sustainable development of agriculture